Клінічні особливості серцево-судинної патології у хворих на цукровий діабет 2-го типу залежно від ступеня порушення функції нирок - Козловська, Х. Ю. (Clinical Endocrinology and Endocrine Surgery, 2011)
Dysfunction of the cardiovascular system and kidneys are presented for patients with type 2 diabetes mellitus. In case of obvious proteinuria clinical signs of cardiovascular diseases were observed in patients with type 2 diabetes mellitus such as more expressed hypertrophy of myocardium, frequent diastolic dysfunction of the left ventricle, decline of retractive function of myocardium. Negative influence of hyperinsulinemia and insulin resistance is set on the state of myocardium at all stages of development of diabetic nephropathy. Arterial hypertension in an identical degree influences on myocardium in both groups of patients, however in the group of patients with proteinuria arterial hypertension is the main damaging factor of kidney dysfunction.